Підготовка кадрів з вищої освіти - Додатко, О. І. (Видавництво НГУ, 2014)
Розглянуто проблеми планування та проведення учбового процесу на прикладі сучасних вищих навчальних закладів. Надано практичні рекомендації щодо оптимізації надлишкових проміжних контрольних заходів та форм звітності.

The planning and conducting educational process problems are considered as an example of modern Higher Educational Institution. Suggested by authors practical recommendations for optimizing redundant intermediate control measures and reporting forms suggested are considered.
Training for higher education
Keywords: професійна компетентність; проблема в його функції як засобу формування професійних компетенцій; основні поняття професійної підготовки майбутніх інженерів; professional competence; basic concepts of professional training of future engineers; a problem in its function as the means of forming professional competences